1976
DOI: 10.1111/j.1365-2141.1976.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic Effect of Two Sulphonamides Evaluated by a New Method

Abstract: A technique to investigate drugs which could cause haemolysis in subjects deficient in glucosc-6-phosphate dehydrogenase (~-glucose-6-phosphate: NADP oxidoreductase; G6PD) has been developed. The method is based on the technique of '"CO, evolution during the incubation of normal erythrocytes in the presence of [~-~~C]glucose and their own serum, the latter containing the active metabolites of the drugs received by normal subjects. By this method agents causing a stimulation of the hexosetnonophosphate pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…63 Perhaps the most attractive of these is the use of plasma from a normal subject ingesting the drug and determining whether it increases metabolism by way of the hexose monophosphate shunt. 64 Another area of importance is the most devastating result of G6PD deficiency: kernicterus. There has been a resurgence of severe neonatal jaundice and kernicterus in recent years, and G6PD deficiency is one of the causes.…”
Section: What Remains To Be Done?mentioning
confidence: 99%
“…63 Perhaps the most attractive of these is the use of plasma from a normal subject ingesting the drug and determining whether it increases metabolism by way of the hexose monophosphate shunt. 64 Another area of importance is the most devastating result of G6PD deficiency: kernicterus. There has been a resurgence of severe neonatal jaundice and kernicterus in recent years, and G6PD deficiency is one of the causes.…”
Section: What Remains To Be Done?mentioning
confidence: 99%
“…Thus, HMS stimulation capacity of a drug may not serve as a reliable indicator of "hemolytic toxicity", as has been suggested (Welt et al, 1971;Gaetani et al, 1976;Pescarmona et al, 1982). It would appear that those compounds designated "Methylene Blue-like" by Carson et al (1981) may elicit HMS activity elevation without toxic oxidation and, therefore, may be unsuitable for use in hemolytic toxicity screening procedures utilizing the HMS stimulation capacity criterion.…”
Section: Hms Activity Measurementsmentioning
confidence: 84%
“…It has been proposed that the capability of a drug to stimulate the HMS in normal red cells would reflect a potential for hemolytic toxicity in G6PD-deficient erythrocytes (Welt et aI., 1971;Gaetani et al, 1976;Pescarmona et al, 1982). Since it is not the HMS per se that reverses oxidative damage, one must presume that the elevation of HMS activity observed under drug treatment is directly coupled to oxidative challenge (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The rela tively small functional defect (about 20%) of the pentose phosphate pathway de tected (table 3) in the patient's erythro cytes seems to be inconsistent to the severe enzymatic deficiency (95%), as detected by the maximum G6PD activity measure ments after assays in proper haemolysates. However, it has been reported that haemo lysis in G6PD deficiency, being intimately related to the red blood cell survival, de pends rather on the function of the pen tose phosphate pathway in the intact erythrocyte than on the maximum G6PD activity as assayed in haemolysates [Yo shida, 1973;Gaetani et al, 1974Gaetani et al, , 1976. The possibility that the impaired pentose phosphate pathway function detected by the glucose utilization test was due to 6PGDH deficiency, was excluded after 6PGDH activity measurement.…”
Section: Discussionmentioning
confidence: 99%